The Ungrateful Muse: Jonathan Swift's 'A Panegyrick on the Dean' and Other Poems. (4th May 2017) - Cook, Daniel
Abstract: An indiscriminately allusive, aggressively intertextual poem, 'A Panegyrick on the Dean, in the Person of a Lady in the North', is both an audacious celebration of Swift's public life in writing and a mock‐panegyric that quietly, condescendingly, queries his own continued relevance as a political commentator during his retreat from Dublin. In foolhardily attempting to prolong his career by indoctrinating his 'grateful' young disciple, a confessed hater of books, in building an unseemly outhouse to mark his diminished value in Ireland and in refusing to be bettered by rival satirists, Swift ironically commemorates himself as a mere writer of libels.